Leadership Lessons from the Battle of Uhud - Amran Rasli; Salman Bashir Memon; Silvi Asna Prestianawati; Imelda Hermilinda Abas (Journal of Islamic Thought and Civilization, 2024)
The current study aimed to probe into leadership lessons from the battle of Uhud by discussing the said historical event followed by the presentation of lessons. The first lesson learned from the battle is the importance of reliable information. When an information is confirmed to be accurate, the top management may plan how to react accordingly before discussing and deliberating on other options with the subordinates. The second lesson learned is that even when the management has different opinions and plans from what the leader has proposed, they must agree on a specific plan accordingly. The third lesson taught by the battle is to be the first-mover advantage in management. A company may outperform its competitors by being the first to market in a new product category. The fourth lesson maximises the advantage of a small group and follows the instructions based on a carefully laid out plan. The fifth lesson uses spiritual motivation to bring a sense of purpose that mobilises human potential in obedience to God’s guidance. The next lesson promotes important qualities of trustworthy followers, that is, obedience, courage, and jihadist mentality. The seventh lesson learned is the need to abide by the concept of “we hear and we obey” (sami’na wa ato’na) as a part of trust (amanah). The final lesson learned from the battle is that if one wants to engage in any endeavour, one must do so properly and leave everything to Allah (tawakkal ala Allah).